Textual and linguistic norms of official documents - N V Alontseva; S B Tomashevich (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
The article focuses on the lexical, grammatical and stylistic features of the official texts. The main stylistic features of the official texts are determined.